Lepidoptera of Arkhangelsk oblast of Russia: a regional checklist - Kozlov, Mikhail; Kullberg, Jaakko; Zverev, Vitali (Entomologica Fennica, 2014)
The first regional checklist of moths and butterflies of Arkhangelsk oblast of Russia includes 1,036 species (538 species of microlepidoptera and 498 species of macrolepidoptera), 496 of which have been found in the oblast for the first time. The most interesting records include Gnorimoschema robustella, Caryocolum leucomelanella, Dichrorampha sequana, D. uralensis, Neptis rivularis and Melitaea phoebe. We also discovered several populations of Parnassius mnemosyne in the southern part of the oblast. The fauna of Arkhangelsk oblast appears poorer than the fauna of Northern Ural Mts. but still includes some Siberian taiga species which do not reach Fennoscandia. Also, the distribution limits of several species extend further north in Arkhangelsk oblast than in the more western parts of Europe.We estimate that 500 to 800 species remain to be found in the study region.